WASTEFUL GOVERNMENT SPENDING AND MARKET DISTORTION: AN EMPIRICAL ACCOUNT OF MODERN INTERVENTIONISM’S UNINTENDED CONSEQUENCES IN PUBLIC PROCUREMENT - , Erick Behar-Villegas (REVISTA PROCESOS DE MERCADO, 2024)
Wasteful government spending can be seen in the Misesian tradition as a type of interventionism with unintended consequences, such as market distortion and the creation of privilege. An underlying problem that helps the distortion become a tradition is that of ‘wasteful spending cultures’. The latter reflects a hardly identifiable problem in practice, i.e. the creation of welfare losses through public administration practices that are influenced by bureaucratic inertia. The growing acceptance of the compatibility of the Austrian tradition and public policy studies allows for a better understanding of imperfect policies, their consequences, and ways to improve both the process and its result. Using data from government-driven procurement of armored cars in Colombia, this paper illustrates how the distortion of the market mechanism is affected by narrative-driven practices and how special interest groups derive rents at the expense of citizens. Using a cost-effectiveness analysis, the study identifies how a tradition is built around procuring high-end vehicles, portraying a failed central planner in the modern public administration context of a developing country.